Environing as Embodied Experience—A Study of Outdoor Education as Part of Physical Education - Lundvall, Suzanne; Maivorsdotter, Ninitha (Frontiers in Sports and Active Living, 2021)
The development of a re-understanding or re-investigation of body pedagogy is currently prominent in the field of physical education (PE) and sport pedagogy. This goes for the learning of movement capability and health but also in relation to outdoor education (OE). The latter a criticized area for having a one-size-fits-all approach to curriculum, with less attention to what to learn in OE, including aspects of everyday practices of being outdoors. The aim of this study was to explore students aged 15 years, and their meaning making of being outdoors expressed in written stories about a favorite place. Two school year eight classes in a Swedish compulsory school situated in an area with high diversity participated. Through this theory-generated empirical study, written stories were explored as one way of evaluating students' meaning making of outdoor places. By using practical epistemology analysis (PEA) to examine experience operationalized through aesthetic judgements attention is paid to the relation between the student and the situation (their favorite place). The analysis make it possible to discern a sense and meaning making of “being” outdoors as an embodied experience, as a relational whole of the self, others and the environment. Descriptions of aesthetic experiences were analyzed leading to dimensions of environing described as “calm and privacy,” “community and togetherness” and “feelings and senses.” A favorite place was by all students described as a very local and nearby place accessible in everyday life. The analysis generated understandings of feelings of “fulfillment” and different embodied experiences of what an encounter with an outdoor place or being outdoors could mean. Furthermore, how personal and diverse the meaning making place tends to be and how experience and habits contribute to the students' creation of microenvironments. Dimensions of environing become part of an embodied process. The analysis of the written stories calls for an alternative understanding of what OE can or should consist of. The findings encourage teachers and researchers to consider alternative understandings and practices of OE that highlight and educate students' overall embodied (individual) experiences and learning in OE and PE.